English Learning Using Pronouncing the Rhyme Method - Sari Rejeki; Henny Suharyati (UNIVERSITAS PAKUAN, 2017)
The study aims to seek the kinds of phonological interference in the English pronounciation of teachers of North Bogor PAUD. The study is a descriptive qualitative research where data is collected by recordings, transcribing and identifying pronunciation difficulties. Based on the findings, factors such as intereference, the differences in the sound system in the two languages affect the teachers pronunciation. It is evident in the data the teachers of PAUD experienced difficulties in pronouncing the consonant phonemes /p/, /k/, /g/, /d/, /s/, //, and the vowel phonemes /?/, //. Diphthongs and stress are also a source of constraint. Keywords: interference, phonemes, diphthongs.